Transcription coupled repair of 8-oxoguanine in murine cells: The Ogg1 protein is required for repair in nontranscribed sequences but not in transcribed sequences - Le Page, Florence (The National Academy of Sciences, 2000)
To assess the role of the Ogg1 DNA glycosylase in the transcription-coupled repair (TCR) of the mutagenic lesion, 7,8-dihydro-8oxoguanine (8-OxoG), we have investigated the removal of this lesion in wild-type and ogg1(−/−) null mouse embryo fibroblast (MEF) cell lines. We used nonreplicating plasmids containing a single 8-OxoG·C base pair in a different assay that allowed us to study the removal of 8-OxoG located in a transcribed sequence (TS) or in a nontranscribed sequence (NTS). The results show that the removal of 8-OxoG in a wild-type MEF cell line is faster in the TS than in the NTS, indicating TCR of 8-OxoG in murine cells. In the homozygous ogg1(−/−) MEF cell line, 8-OxoG was not removed from the NTS whereas there was still efficient 8-OxoG repair in the TS. Expression of the mouse Ogg1 protein in the homozygous ogg1(−/−) cell line restored the ability to remove 8-OxoG in the NTS. Therefore, we have demonstrated that Ogg1 is essential for the repair of 8-OxoG in the NTS but is not required in the TS. These results indicate the existence of an Ogg1-independent pathway for the TCR of 8-OxoG in vivo.